The value of serum zinc, copper, ceruloplasmin levels in patients with gastrointestinal tract cancers - Alper BOZ,; Osman EVLİYAOĞLU,; Mehmet YILDIRIM,; Nazif ERKAN,; Baysal KARACA, (Turkish Journal of Gastroenterology, 2019)
-